Penerapan Metode Estafet Writing dalam Keterampilan Menulis 汉字 (hànzì) Siswa Kelas VIII SMP Frater Makassar - Jumria Febrianti; Ambo Dalle (Universitas Negeri Makassar, 2022)
This study aims to improve the writing skills of (hànzì) class VIII students at SMP Frater Makassar through the application of Estafet Writing method. The subjects of this study were the 30 students of class VIII E SMP Frater Makassar. This research is classroom action research which consists of two cycles. This research data consists of two types, namely: qualitative data and quantitative data. Qualitative data was obtained through observation, while quantitative data was obtained through writing skills tests in cycles I and II. The results showed that the writing skill (hànzì) with the average score of the writing skill test (hànzì) obtained by students from 69.43% with sufficient category in the first cycle increased to 78.1% with the good category in the second cycle. These results indicate that the application of Estafet Writing method can improve the writing skills of (hànzì) class VIII E students at SMP Frater Makassar. Keywords: Estafet Writing, Writing Skills, (hànzì), Chinese Language